Using Artificial Intelligence Tools to Develop Students’ Foreign Language Communicative Competence in Wartime - Lemeshchenko-Lagoda, Viktoriia; Лемещенко-Лагода, Вікторія Володимирівна; Kryvonos, Iryna; Кривонос, Ірина Анатоліївна (My University, 2025)
This article examines the use of AI-based tools to develop students’ foreign-language communicative competence in wartime higher education in Ukraine. It reports findings from a 12-week quasi-experimental study conducted at Dmytro Motornyi Tavria State Agrotechnological University under conditions of relocation and fully online learning. Eight third- year student groups (N = 104) were divided into a control group receiving standard distance instruction and an experimental group using AI-supported tools for speaking, listening, reading, and writing. Pre- and post-testing showed improvement in both groups, but gains were stronger in the experimental group, especially in speaking (+15 percentage points) and listening (+17 percentage points). Reading and writing also improved, although less markedly. Questionnaire data further indicated increased motivation, engagement, and satisfaction with personalised feedback among students using AI. The findings suggest that AI can serve as a compensatory pedagogical resource in emergency online language education by expanding opportunities for oral practice and flexible self-study. At the same time, its use requires teacher guidance, attention to academic integrity, and awareness of unequal digital access.
Keywords: communicative competence; distance learning; higher education; wartime education; English for Specific Purposes (ESP); Ukraine